PENGEMBANGAN BUKU AJAR MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN BERPERSPEKTIF KESETARAAN GENDER PADA SEKOLAH DASAR KELAS LIMA DI KABUPATEN INDRAMAYU - Nunung Nurjanah; Ratna Dewi Lestyorini (Sinau : Jurnal Ilmu Pendidikan dan Humaniora, 2019)
The background of this study is the lack of understanding of gender equality in elementary school students which raises various attitudes and actions that tend to be discriminatory and unfair to one party, especially felt by female students. The purpose of this study is to build students' understanding of gender equality through the development of citizenship education textbooks for the fifth grade of elementary schools in Indramayu Regency. The research approach used is the Reaserch And Development (R & D) research. The subjects in this study were fifth grade elementary school students in Indramayu Regency who were used as research samples. The number of schools studied were 18 elementary schools from the western part of Indramayu, central part of Indramayu and eastern part of Indramayu. The results of the study show that students understanding of gender equality changes and is better after obtaining Pancasila and Civic Education subject matter by paying attention to the equality of Gender contained in the book on gender Pancasila and Civic Education compiled by researchers.